2018
DOI: 10.1177/0272684x18773763
|View full text |Cite
|
Sign up to set email alerts
|

Suspended Life Pattern: A Qualitative Study on Personal Life Among Family Caregivers of Hemodialysis Patients in Iran

Abstract: Purpose To determine the personal life of family caregivers of patients undergoing hemodialysis. Methodology In this qualitative study, individual semistructured interviews were carried out with 19 caregivers of hemodialysis patients. All interviews were recorded, typed, and imported into the Open Code Software. The Graneheim and Lundman's content analysis approach was used for the analysis. Findings The theme of this study was suspended life pattern that was extracted from two categories of "Imbalance between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 26 publications
2
37
0
4
Order By: Relevance
“…We suggest that Thompson's () framework focusing on components may also be applied to the next of kin. Ebadi et al () called for improved interaction among professional caregivers to understand the conditions of the next of kin, thereby improving the quality of life for both patients and their families.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We suggest that Thompson's () framework focusing on components may also be applied to the next of kin. Ebadi et al () called for improved interaction among professional caregivers to understand the conditions of the next of kin, thereby improving the quality of life for both patients and their families.…”
Section: Discussionmentioning
confidence: 99%
“…These symptoms were more prominent in female spouses (Liedstrom et al, 2014). Ebadi, Sajadi, Moradian, & Akbari (2018) found that the next of kin of patients undergoing haemodialysis experienced unpredictable, uncontrollable stressors such as time conflicts between caregiving and occupational affairs, care-induced fatigue and fear of the future. Aasen et al (2011) showed that the next of kin of elderly patients on HD felt excluded and forgotten by health providers.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…The breadth of care required for a patient with ESKD causes the caregiver to be more vulnerable to emotional, physical, and psychological consequences, which are essentially greater in countries with more limited resources (3). The complications in caring for a patient receiving hemodialysis aggravate depression and reduce the quality of life of the caregiver (4). The burden on the caregiver directly affects the quality of care provided by them and may lead to inadequate care or even the abandonment of patient (5).…”
Section: Introductionmentioning
confidence: 99%
“…Admittedly, caregivers and families of patients receiving hemodialysis have not been well understood, and what has been in the spotlight was primarily the patient receiving hemodialysis, not his or her caregiver. Limited studies have looked at the personal lives of caregivers of these patients (4). In one qualitative study, caregivers of patients receiving hemodialysis suffered from burden which formed four categories: care challenge, psychological vulnerabilities, the chronic nature of care and care in the shade.…”
Section: Introductionmentioning
confidence: 99%